2007
DOI: 10.1074/jbc.m701789200
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Signals and Mechanisms Mediating Nuclear Trafficking of GATA-4

Abstract: Nucleocytoplasmic transport of GATA-4 is important in maintaining and regulating normal cardiogenesis and heart function. This report investigates the detailed mechanisms of GATA-4 nuclear transport. We characterized a nonclassical nuclear localization signal between amino acids 270 and 324 that actively transports GATA-4 into the nucleus of both HeLa cells and cardiac myocytes. Fine mapping studies revealed four crucial arginine residues within this region that mediate active transport predominately through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 60 publications
3
5
0
Order By: Relevance
“…R264A is able to activate the promoter containing a tandem GATA-site similarly to wtGATA4, in contrast to K299A, which was unable to bind this sequence properly and to activate transcription. These results and their interpretation are consistent with the work of Philips et al [ 43 ], who showed that mutation of R283 and K299 reduces DNA binding to a monomeric GATA element. Alterations in the packing of C- and N-terminal zinc fingers may thus be the cause for the strongly reduced GATA4-NKX2-5 physical interaction detected with these mutants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…R264A is able to activate the promoter containing a tandem GATA-site similarly to wtGATA4, in contrast to K299A, which was unable to bind this sequence properly and to activate transcription. These results and their interpretation are consistent with the work of Philips et al [ 43 ], who showed that mutation of R283 and K299 reduces DNA binding to a monomeric GATA element. Alterations in the packing of C- and N-terminal zinc fingers may thus be the cause for the strongly reduced GATA4-NKX2-5 physical interaction detected with these mutants.…”
Section: Discussionsupporting
confidence: 92%
“…Since all mutations were located outside the antibody recognition site, western blots were used to quantify the mutant protein levels produced in mammalian COS-1 cells. All mutant proteins are expected to localise to the nucleus like native GATA4 since single amino acid substitution in zinc finger area is not sufficient to inhibit the nuclear trafficking [ 43 , 44 ]. Physical interactions with NKX2-5 were assessed in co-immunoprecipitation with N-terminal FLAG-NKX2-5 and analysed by western blots using GATA4 and NKX2-5 antibodies ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results show a direct correlation between loss of DNA binding activity and accumulation in nuclear speckles. Similar behavior was recently described for the transcription factor GATA-4, although the subnuclear compartment to which it localized was not identified [67]. Although we cannot ignore that the elimination of the DNA binding domains may result in a conformational change that exposes the His-repeat, we favor a loss of retention in the chromosomal compartment as being responsible for the enrichment in nuclear speckles.…”
Section: Discussionsupporting
confidence: 75%
“…EGFP-SUMO-1 has been previously described [25] and was kindly provided by Hisato Saitoh (Picower Institute of Medical Research, New York, NY). The brain natriuretic peptide (BNP) reporter construct and pMT3-HA-SUMO-1 have been previously described [19], [26]. FLAG-SENP-1 (Addgene plasmid 17357) and FLAG-SENP-8 (Addgene plasmid 18066) were kindly provided by Edward Yeh (University of Texas, Houston, TX) [27], [28].…”
Section: Methodsmentioning
confidence: 99%
“…For protein expression, COS-7 cells were grown on 100 mm-diameter Petri dishes and transfected with 1–2 µg of FOG-2 and its derivatives, SUMO-1 or GFP-SUMO-1 expression vectors using Lipofectamine2000 following the manufacturer’s instructions (Invitrogen). HeLa cells used for luciferase assays were cultured in 6-well plates and were transfected with 300 ng of pGL3-Basic-BNP reporter [26], 300 ng of pCS2+GATA-4, 50 to 400 ng of pCS2+FOG-2, pCS2+FOG-2-4KR or SUMO-1-FOG-2-4KR, 50 to 300 ng of GFP-SUMO-1 and 500 ng of pFLAG-SENP-1 and pFLAG-SENP-8. The total amount of DNA was kept constant by adding empty pCS2+ vector.…”
Section: Methodsmentioning
confidence: 99%